Efektivitas Penggunaan Business Center Pada Kelas X Bisnis Daring Dan Pemasaran Di SMKN 50 Jakarta - Dyah Syafitri Latifah; Corry Yohana; Maulana Amirul Adha (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the effectiveness of using business center in class X Online Business and Marketing at SMKN 50 Jakarta. The type of research is descriptive research with qualitative approach. Researchers obtain research data through interviews, observation, and documentation. There were 14 informants in this study consisting of school principals, vice principal, administrators business center, teaching staff, and 6 students. Based on research results, the effectiveness of using business center in class X Online Business and Marketing at SMKN 50 Jakarta has been effective, but there are several things that need attention because they have not run optimally. This is reviewed from several indicators of effectiveness which include: (1) input effectiveness of using business center considered effective, user business center are teachers and students. Facility business center is quite complete although there are still deficiencies. Spatial business center is neat enough and product placement is in accordance with its category. Management business center good enough and there is a clear organizational structure. (2) process effectiveness of using business center considered to be quite effective, practice activities were carried out in accordance with procedures even though standard operating procedures were not yet available in business center. There are some students who do not obey the rules. Practices take place according to a predetermined schedule. (3) output effectiveness of using business center considered to be effective, practice activities are running in accordance with procedures and objectives business center. The results of practice can provide benefits for schools and school members. Keywords: Effectiveness, Business center, Online Business and Marketing